Actual role and problems of compensation management in Croatian enterprises: An empirical study - Lovorka Galetić; Darko Tipurić; Božidar Juri (Journal for East European Management Studies, 2000)
The article deals with current positions and perspectives of compensation management in Croatian enterprises. To confirm the hypothesis that neither enough attention to compensation management has been paid, nor the influence, which it has on prosperity, efficiency and enterprises' competitiveness, has been recognized in a sufficient degree in the Republic of Croatia, the authors present an empirical study conducted at the beginning of 1998 on the sample of 139 Croatian enterprises. Various aspects of compensation management from the point of view of the enterprise size, realized financial results of the enterprise, kind and profitability of the enterprise belonging activity have been analyzed. – – In diesem Artikel werden aktuelle Positionen und Perspektiven des Managements von Vergütungssystemen in kroatischen Unternehmen dargestellt. Mit dieser empirischen Studie, die Anfang 1998 mit 139 kroatischen Unternehmen durchgeführt wurde, wollen die Autoren die Hypothese belegen, daß dem Management von Vergütungssystemen nicht genügend Aufmerksamkeit zuteil wird. Außerdem wird seine Bedeutung für das Wachstum, die Effizienz und die Wettbewerbsfähigkeit eines Unternehmens unterschätzt. Verschiedene Aspekte des Managements von Vergütungen werden in dieser Studie betrachtet.
Keywords: 650